Motehen: A Case Study of Shifting Perceptions of Japanese Masculinity and Desirability Through Study Abroad - Morinaga-Williams, Elisabeth (Libby) (Journal of International Students, 2018)
Topics of gender, sexuality and desirability have become prominent themes in study abroad research, particularly when exploring the experiences of Japanese women overseas. However, little research has explored the gendered experiences of Japanese male international students. This paper presents the case study of Ki, a young Japanese man who studied abroad in the United States. During his sojourn, Ki experienced a significant shift in his perceptions of masculinity and desirability through clashes with essentialized Western romantic practices and gender norms. This article critically examines discriminatory discourses of Japanese heterosexual masculinity and argues that colliding with these discourses negatively altered Ki’s view of himself as a desirable romantic partner both during his sojourn and upon his return to Japan.